Pengaruh Kecepatan Kendaraan Akibat Pemasangan Speed Bump: Model Greenberg - Faradilla, Cut Meutia; Abdullah, Zulfhazli; Mukhlis, Mukhlis; Usrina, Nura; Fithra, Herman; Fikry, Muhammad (Akademi Komunitas Negeri Aceh Barat, 2025)
AbstractA speed bump is a traffic engineering tool designed to control vehicle speed, particularly in residential areas, to enhance the safety of pedestrians and cyclists. This study employs the Enter and Stepwise methods using SPSS to analyze the impact of speed bumps on vehicle speed and related variables. The study results indicate that the relationship between installation distance (X4) and vehicle speed in area 3 (Y) for motorcycles is given by Y = 5.647 + 0.264 X4 with R² = 0.887. In contrast, for light vehicles, it is Y = 3.381 - 0.253 X4 with R² = 0.920. Among the five locations studied, location 2 exhibited the strongest correlation between speed, volume, and density, with a coefficient of determination (R²) greater than 0.5. In area 2, the relationship between volume and speed when crossing a speed bump has R² = 0.512. Meanwhile, in area 3, between speed bumps, the relationship between volume and density shows R² = 0.904, and the relationship between speed and density is R² = 0.804. These findings indicate that speed bumps' height and installation distance significantly impact vehicle speed patterns. Additionally, the relationship between volume, speed, and density is notably strong at several research locations. AbstrakAlat pengendali kecepatan atau Speed bump merupakan alat rekayasa lalulintas yang berfungsi untuk mengendalikan kecepatan kendaraan yang melintas disuatu ruas jalan, terutama di permukiman penduduk guna melindungi pejalan kaki dan pengendara sepeda. Penelitian ini menggunakan metode Enter dan Stepwise menggunakan software SPSS untuk mengenalisis speed bump terhadap kecepatan dan variabel terkait. Hasil penelitian didapatkan bahwa hubungan jarak pemasangan (X4) dengan kecepatan kendaraan pada area 3 (Y) untuk sepeda motor diperoleh Y=5.647 + 0.264 X4 dengan R2 =0.887, dan kendaraan ringan Y=3.381 - 0.253 X4 dengan R2=0.920. Dari lima lokasi yang diteliti, hubungan antara kecepatan, volume, dan kerapatan menunjukkan korelasi terkuat di lokasi 2, dengan nilai koefisien determinasi (R²) 0,5. Pada area 2, hubungan antara volume dan kecepatan saat melintasi speed bump memiliki R² = 0,512. Sementara itu, hubungan antara volume dan kerapatan di area 3, yaitu di antara speed bump, menunjukkan R² = 0,904. Hubungan antara kecepatan dan kerapatan di area yang sama (area 3) memiliki R² = 0,804. Hal ini mengindikasikan bahwa tinggi dan jarak pemasangan speed bump memiliki dampak yang signifikan terhadap pola kecepatan kendaraan, serta hubungan antara volume, kecepatan, dan kepadatan memiliki keterkaitan yang kuat di beberapa lokasi penelitian.